PENYULUHAN HUKUM TENTANG BANTUAN HUKUM CUMA-CUMA UNTUK MASYARAKAT TIDAK MAMPU UNTUK WARGA KAMPUNG SUKADANA 1 KELURAHAN KASEMEN KECAMATAN KASEMEN KOTA SERANG - Anton Aulawi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The need for an understanding of the existence of a free legal aid program for the poor is very important for the public to know. The Head of Youth Leaders from Sukadana 1 Village, Kasemen Village, Kasemen District, Serang City asked the community service team from the Jatramada Legal Aid Institute to provide legal counseling for the community. There are many people who do not know about the existence of free legal aid programs, namely the poor when they face legal problems will get free services with assistance from Legal Aid Organizations accredited by the Ministry of Law and Human Rights with assistance costs law borne by the State. This community service activity in the form of legal counseling was carried out on Monday 24 February 2020, at Mr. Faiz's house, Sukadana 1 RT 01 RW 03, Kasemen Village, Kasemen District, Serang City, and the community who attended the event was the RW Chairman. 003, Head of RT, community leaders and residents of Sukadana 1. This activity starts at 19.30 PM until 21.30 PM. The number of participants who attended was as many as 40 people. The results of the socialization of free legal aid for the poor is for partners, namely the people of Kampung Sukadana 1, of course an increase in understanding of Law Number 16 of 2011 concerning Legal Aid, which explains about free legal aid for the poor, apart from that legal counseling partners / participants also gain knowledge about legal skills when facing minor legal problems.